2000
DOI: 10.1002/1096-9098(200005)74:1<15::aid-jso4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with sulindac in familial adenomatous polyposis: Is there an actual efficacy in prevention of rectal cancer?

Abstract: Sulindac appears to influence the morphological appearance of polyps in FAP patients, inducing apparent regression. However, at a dose of 200 mg, it does not influence the progression of polyps toward a malignant pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 31 publications
1
52
0
4
Order By: Relevance
“…In one prospective study, patients with FAP treated with sulindac maintained an antitumor response at a mean of 63.4 months of treatment (36). In another study, rectal adenomas regressed significantly during the first 6 months of sulindac use, but after a mean of f48 months of treatment both number and size of adenomas increased, showing no statistical difference with baseline values (37). Case reports also indicate that patients with FAP chronically maintained on sulindac for tumor suppression can develop invasive adenocarcinomas (38), an occurrence also seen in one of the Min/+ mice treated long-term with celecoxib (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In one prospective study, patients with FAP treated with sulindac maintained an antitumor response at a mean of 63.4 months of treatment (36). In another study, rectal adenomas regressed significantly during the first 6 months of sulindac use, but after a mean of f48 months of treatment both number and size of adenomas increased, showing no statistical difference with baseline values (37). Case reports also indicate that patients with FAP chronically maintained on sulindac for tumor suppression can develop invasive adenocarcinomas (38), an occurrence also seen in one of the Min/+ mice treated long-term with celecoxib (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, doses of sulindac 150-200 mg a day appeared ineffective. 88,95 A non-randomized controlled study showed the efficacy of rectal administration of sulindac 300 mg a day against rectal adenomas. 97 Also, indomethacin suppositories regressed rectal polyps in a non-controlled series of patients at a dose of 100 mg, but not 50 mg a day.…”
Section: Nsaids and Cox-2 Inhibitors For Colon Cancer Preventionmentioning
confidence: 99%
“…[39][40][41]43,49,78,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Endpoints are number and size of adenomas measured by flexible sigmoidoscopy or colonoscopy. All studies report complete or partial regression of adenomas after 3-6 months of treatment with sulindac 300-400 mg a day.…”
Section: Nsaids and Cox-2 Inhibitors For Colon Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulindac therapy is recommended in FAP patients after subtotal colectomy with IRA (48). However, rectal cancer has developed in patients in whom rectal polyps were effectively controlled with sulindac (49)(50)(51). In addition, sulindac appears to lack significant benefit in regressing duodenal adenomas (52) or preventing initial occurrence of adenomas in APC mutation carriers (primary prevention) (53).…”
Section: Chemoprevention Of Colon Cancermentioning
confidence: 99%